Is Group Choice a Part of Economics?: Further Comment - Ellis, Howard S. (Quarterly Journal of Economics, 1953)
Is Group Choice a Part of Economics? Further Comment Howard S. Ellis Howard S. Ellis University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 4, November 1953, Pages 609–613, https://doi.org/10.2307/1883606 Published: 01 November 1953